(untitled) (De Legibus - Law Journal, 2024)
The Rome Statute, wich established the International Criminal Court, sets out 4 jurisdictions established to assess jurisdiction over a specific case. We will analyze the territorial jurisdiction and its specifications. The territorial jurisdiction may not initially ber very difficult to understand. However, such thinking finds no reflection in reality. In this paper, we propose to show the rule (territoriality principle) and then enunciate some deviations from himself. Namely, when the International Criminal Court will hear a case, even if is not in the presence of a State Party, and its opposite, when the principle of territoriality is complied with, even so, the Court will refrain from replay to he case. Finally, we will leave some critical reflections regarding the Rome Statute and, in particular, the criterion of territorial jurisdiction adopted.